Effect of different low-level intensity laser therapy (LLLT) irradiation protocols on the osseointegration of implants placed in grafted areas (Journal of Applied Oral Science, 2021)
Objective: To evaluate the effect of different protocols of low-level intensity laser therapy (LLLT) irradiation on the osseointegration of implants placed in grafted areas. Methodology: 84 rats were randomly allocated into six groups: DBB: defect filled with deproteinized bovine bone; HA/TCP: defect filled with biphasic ceramic of hydroxyapatite/β-tricalcium phosphate ; DBB-LI: defect filled with DBB and treated with LLLT after implant placement; HA/TCP-LI: defect filled with HA/TCP and treated with LLLT after implant placement; DBB-LIB: defect filled with DBB and treated with LLLT after graft procedure and implant placement; and HA/TCP-LIB: defect filled HA/TCP and treated with LLLT after graft procedure and implant placement. The bone defects were made in the tibia and they were grafted. After 60 days, the implants were placed. The rats were subsequently subjected to euthanasia 15 and 45 days after implant placement. The pattern of osseointegration and bone repair in the grafted area was evaluated by biomechanical, microtomographic, and histometric analyses. Furthermore, the expression of bone biomarker proteins was assessed. Results: The LLLT groups presented higher removal torque, mineralized tissue volume, and a greater degree of osseointegration, especially when LLLT was performed only after implant placement, and these findings were associated with higher expression of BMP2 and alkaline phosphatase. Conclusion: LLLT performed on implants placed in grafted areas enhances the osseointegration process.